LIS education and training in Portugal - Ribeiro, Fernanda (2009)
This article starts by a brief overview of the evolutive process in the field of education in Library and Information Science (LIS) in Portugal and its connection with international contexts. This approach allows to understand the paradigm shift and the crucial and complex changes caused by the impact of social, economic, cultural and technological conditions of the information era as well as the emergence of a new scientific area - Information Science (IS). Both contributed to the arising of new perspectives in information services, new information professionals and, undoubtedly, new education models. Considering the positioning in the European space, will also be considered the implementation of the European Higher Education Area, whose creation endeavoured an educational approach across the European Union countries, including LIS field.